Quasi-static thermal modelling of multi-scale sliding contact for unlubricated brush seal materials - Xia, Q; Gillespie, D; Owen, A; Franceschini, G (American Society of Mechanical Engineers, 2019)
Prediction of contact temperature between two materials in high speed rubbing contact is essential to model wear during unlubricated contact. Conventionally assumptions of either steady or an annular heat sources are used for slow and high speed rottion respectively. In this paper, a rotating heating source is solved using an in-house finite element method code. This captures the full geometry and rotating speed of the rubbing bodies. Transient heat transfer is modelled quasi-statically, eliminating the need for a transient 3D simulation. This model is shown to be suitable for contact temperature prediction over a wide range of rotating speeds, anisotropic thermal conductivity, and non-uniform thermal boundary conditions. The model calculates heat partition accurately for a thin rotating disc and short pin combination, which cannot be predicted using existing analytical solutions. The method is validated against Ansys Mechanical and experimental infra-red thermography. Results demonstrate that the annular source assumption significantly under-predicts contact temperature, especially at the rubbing interface. Explicit modelling of a thin disc results higher heat partition coefficients compared with the commonplace semi-infinite length assumption on both static and rotating components. The thermal anisotropy of tuft-on-disc configurations is evaluated and compared to a uniform pin-on-disc configuration. Despite the effective thermal conductivity in the bristle tuft being approximately one order of magnitude lower than along the bristle length (treating the bristle pack as a porous medium), its impact on heat partition and contact temperature is shown to be limited.